Completeness and legibility of obstetric referral documents from peripheral public health facilities to a tertiary care facility in North India- a cross-sectional study - Arunima Saini; Monika Agarwal; Vijay Kumar Singh; Anjoo Agarwal; Seema Tandon; Sugandha Jauhari (Elsevier, 2023)
Introduction: Incomplete information in the referral letters may result in a delayed diagnosis, polypharmacy, and wasteful duplication of laboratory testing, which negatively impact patient care. The aim of the present study was to assess the quality (completeness and legibility) of obstetric referral documents sent by health personnel of lower-level public health facilities to a tertiary health care facility. Methodology: A cross-sectional study was conducted among 675 pregnant women referred to a tertiary care centre from public health facilities of Lucknow and other districts of the state of Uttar Pradesh, from October 2019 to September 2020. Systematic random sampling was used to select the study participants. Data was analysed using Statistical Package Social Sciences 24 and presented as frequencies, percentages, and graphs. A p-value <0.05 was considered statistically significant. Results: About two-third (377/622) of the referrals had the information on the pre-referral treatment but it was not readable in (127/269) of those forms. Less than half (269/622) referral letters had information for the medication dosage but in only (142/269), it was clearly written. First referral unit-community health centres scored less for quality of referral letter in comparison to non-first referral unit-community health centres. Conclusion: The study concluded that there was poor documentation of the referral letters at all levels of healthcare facilities. Health personnel need to be sensitized for importance of completeness of information in the referral letters to improve the treatment as well as the outcome.